Psychological Health and Risk Factors of College Students within the Context of the COVID-19 Pandemic: A Cross-Sectional Study - Feilong Lv; Rui Zhu; Xiaorong Hou; Laihao Fang; Yanzhi Wang; Zhiyin Du; Xiaoni Zhong; Jiaxiu Liu (Behavioral Sciences, 2023)
Background: Students are a priority population in mental health research. This study aimed to explore the risk factors of anxiety and depression symptoms among college students in Chongqing, a megacity under the impact of COVID-19, and to provide a basis for determining the priorities of public health policies and implementing effective educational health care interventions. Methods: In this cross-sectional study conducted in Chongqing, China, the data came from web-based stratified random sampling. Anxiety and depression symptoms were measured by the Self-Rating Anxiety Scale (SAS) and the Center for Epidemiological Studies Depression Scale (CES-D), respectively, and risk factors were analyzed by logistic regression. Results: Data were obtained from 915 college students (34.75% were male, and 65.25% were female) with age (20.29 ± 1.51) in Chongqing, China. The prevalence rates of anxiety and depression were 19.78% and 22.62%, respectively. Logistic regression analysis revealed that the risk factors of anxiety symptoms were associated with junior years, sleep time of less than 6 h a day, influence on career planning, and depression symptoms. Comprehensive, science and engineering, and medicine disciplines, having siblings, poorer mastery of study, and anxiety symptoms were risk factors for developing depression symptoms. Conclusions: During the pandemic, college students experienced varying degrees of anxiety and depression. Our research findings highlight the necessity of universities and relevant departments providing precise mental health education for college students under major public health emergencies.